TINJAUAN KRIMINOLOGI TERHADAP TERJADINYA PELECEHAN SEKSUAL (BEGAL PAYUDARA) DI KOTA PONTIANAK - NIM. A1011221150, MAULIDYA AZZARA (Fakultas Hukum Universitas Tanjungpura, 2026)
Abstract Sexual harassment in public spaces is an increasingly prevalent form of moral violation and causes public unrest, particularly among women. One common form of sexual harassment is physical breast groping, known locally as